Kepuasan Mahasiswa terhadap Implementasi E-CRM pada Binus University - Meyliana, Meyliana; W., Henry Antonius E.; Santoso, Stephen W. (Bina Nusantara University, 2012)
Education industry is a service enterprise that has its unique characteristics. Thus, the implementation of e-CRM in education institutions and other service companies is different. The research methodology uses variables Pre-Purchase, At-Purchase, Post-Purchase, e-Trust, e-Satisfaction and e-Loyalty, where the hypothesis was tested by correlation analysis and regression analysis. Besides, it also uses IPA (Importance Performance Analysis) to identify factors to be improved by calculating the gap analysis. The test results obtained show that based on the correlation analysis, all the H1hypotheses (has relationship) are accepted and based on the regression analysis, all the hypotheses H1 (has effects) is accepted. Under the IPA, for both increases in the first priority and second priority, all the variables need to be improved.